Marketing's metaphors have expired: An argument for a new dominant metaphor. (September 2019) - Delbaere, Marjorie; Slobodzian, Adam D.
The discipline of marketing uses many metaphors. Historically, the dominant metaphors in marketing strategy have been adapted from warfare and military science. The purpose of this conceptual article is to analyze and evaluate commonly used warfare metaphors in marketing strategy. A cross-domain comparison of these metaphors and conceptualizations of war are assessed to determine whether they are still appropriate in light of the advancements in both military science and marketing theory. The analysis found that there are many fundamental and questionable differences between these two domains; therefore, a new conceptual metaphor for marketing strategy is proposed.